Stereotyping Low‐Wage Mothers Who Have Work and Family Conflicts. (12th June 2013) - Dodson, Lisa; Williams, Joan C.; Glass, Jennifer; Correll, Shelley; Berdahl, Jennifer L.
<x xml:space="preserve">Abstract</x> This article examines the views of low‐wage mothers about how they are stereotyped when they need work flexibility to care for children. From a decade of qualitative and participative research with low‐income/working class mothers (n = 300) and employers (n = 50) of entry‐level workers, a discourse of "personal irresponsibility" emerged rather than one about work/family conflict. Drawn from interviews and interpretive focus groups, mothers describe being unable to find or buy stable care for children, thus facing trouble at work. While some employers expressed sympathy, others echoed "welfare mother" schema and dismissed low‐wage mothers' conflicts caring for children as the fault of irresponsible reproducers. Implications for a cross‐class work/family movement are discussed.